MEDIA EDUCATION AS THE BASIS FOR THE FORMATION OF MONOLOGICAL SPEECH IN PRIMARY EDUCATION STUDENTS - Chervinska, Inna; Verbeshchuk, Svitlana; Lutsan, Niadia (Mountain School of Ukrainian Carpaty, 2024)
The authors reveal the essence of media education as the foundation for the development of monological speech in primary school students within the New Ukrainian School framework. They highlight the relevance of the issue of high-quality education for students as one of the most pressing social challenges during a period of global innovations occurring in the spheres of economy, culture, and technology. The article emphasizes the findings of researchers on media education issues and its implementation in the educational process. It describes its role and the peculiarities of its influence on the formation of monological speech in primary education students. The methodological basis of the study includes theoretical principles and a range of conceptual ideas reflected in domestic philosophical, pedagogical, and psycholinguistic literature related to the formation of linguistic personality. The research utilized a combination of general scientific methods. Theoretical methods facilitated the generalization and analysis of psychological-pedagogical literature, enabling the identification of key aspects of the issue. Empirical methods were used to gather research material (surveys, analysis of legal and regulatory frameworks) and hold discussions with educators about their readiness to implement ideas, forms, models, and technologies of media education in the development of monological speech among students. The article underscores the importance of organizing the educational process effectively. It highlights that students master various types of activities that develop their speech, ability to communicate, and engage in dialogue with classmates, teachers, parents, and other familiar and unfamiliar individuals. Researchers concur on the significance of contemporary media education in organizing effective interaction during the educational process and developing monological speech in primary school students. The problem of developing the linguistic personality of students during schooling is identified as a complex and multifaceted task requiring theoretical reflection, the search for new methods and approaches, the promotion of constructive ideas, and their experimental verification. Keywords: media education, media literacy,